Cover Feature: Pincer‐Type Mesoionic Carbene Nickel(II) Complexes: Synthesis, Properties, Reactions, and Catalytic Application to the Suzuki–Miyaura Coupling Reaction of Aryl Bromides (Eur. J. Inorg. Chem. 10/2022). Issue 10 (1st March 2022) - Matsubara, Kouki; Tomomatsu, Kanta; Tajiri, Ayame; Watanabe, Arisa; Koga, Yuji; Ishikawa, Ryuta; Yamada, Yuji
Abstract : The Cover Feature shows an image of the final product of an elaborately designed pincer complex derived from triazolylidene, which has emerged through a long series of steps from the earth′s abundant nickel mines. The complex has interesting properties provided by the ligand with strong σ‐donor and π‐acceptor abilities, and bulky substituents. It is also active in the Suzuki‐Miyaura coupling of aryl bromides. The crystals are called annabergite and are known to be a landmark in nickel mining. Like this crystal, the complex is expected to become one of the landmarks for the development of organonickel chemistry. More information can be found in the Research Article by K. Matsubara and co‐workers .